PEMBENTUKAN KARAKTER ANAK MELALUI LAGU KOKONUA - SRI AYU LAALI (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2018)
This study aims to: (1) Describe when the song Kokonua sung in children on the island Kabalutan, (2) Describe where a sung kokonua in children on the island kabalutan, (3) Describe who sang kokonua in children, (4) Describe how to tune kokonua that play a role in shaping the character of children on the island Kabalutan, (5) Describe the reason the song kokonua used in the formation of character, and (6) Describe the values of any character formed through songs kokonua in children aged 5 years on the island kabalutan. The study subjects children aged 5 years totaling 3. This research is a qualitative ethnographic study research. Analysis of the data used is the model Spradley. This research data obtained from observation, documentation, and manufacturing field notes. The findings of this study indicate that: (1) song Kokonua sung in children when the children will sleep at night (2) where dinyanyikaan songs kokonua in children that is at home or in bed, (3) who sings kokonua is a mother and grandmother (4) tune kokonua that play a role in the formation of character that rhythm chirpy: songs kokonua and kokanding, rhythm tunable: goyak-goyak and daughter papu (5) the reason why songs kokonua used for the formation of character that song kokonua is a song traditionally have mystical element that is used to frighten children with a view to the formation of character, and (6) of character values formed in children aged 5 years on the island Kabalutan that is independent, responsible, hardworking, honest, mutual love, togetherness / solidarity, chirpy, patient, resilient and grateful.Keywords: Character, Children, Kokonua Song.